"I'll Show You How to Write My Name": The Contribution of Naturalistic Sibling Teaching to the Home Literacy Environment. Issue 4 (9th August 2017) - Segal, Aviva; Howe, Nina; Persram, Ryan J.; Martin‐Chang, Sandra; Ross, Hildy
Abstract: Research on the home literacy environment has typically involved parents as teachers with little attention given to siblings' roles in teaching each other. This study examines naturalistic language and literacy teaching by 39 sibling dyads, at two timepoints, when children were ages 2 and 4 (time 1; T1) and again at ages 4 and 6 (time 2; T2). Each family was observed for a total of six 90‐minute sessions at both timepoints. First, all sibling‐directed teaching sequences were identified, including instances of formal and informal teaching. Second, sequences were coded for evidence of language (i.e., vocabulary, book concepts, songs, phonological awareness) and literacy concepts (i.e., alphabetic principle, reading, writing, spelling). Over 40% of the T1 and T2 teaching sequences involved language and literacy concepts. Older siblings taught the majority of the time at T1 and T2; however, the number of sequences taught by younger siblings increased proportionally over time. Because siblings taught vocabulary concepts significantly most often at both T1 and T2, further analyses were conducted on vocabulary subcategories (i.e., expansion, discussing pictures, relaying word meaning, checking for listener understanding, second‐language instruction). Significantly more teaching sequences involved expansion than other vocabulary subcategories at both timepoints. Finally, at T2, literacy concepts (i.e., writing, spelling) were taught significantly more than at T1. Our findings demonstrate that siblings are interested in teaching each other a variety of language and literacy concepts during naturalistic interactions in the home, indicating that siblings contribute to the richness of the home literacy environment.